Angular scatter microscopy - Delica, Serafin Famadeco (2004)
A New contrast enhancement mechanism for light microscopy is modeled and experimentally implemented. The technique, which we call angular scatter microscopy, utilizes the different particles to enhance the image contrast. Using Mie theory and Monte Carlo protocol, we model the scattering process through the optical setup for various optical parameters. The technique distinguishes between particles of different sizes provided that the scatterers' sizes are comparable to the wavelength of incident light.